Ultrasound Flow Imaging Study on Rat Brain with Ultrasound and Light Stimulations - Junhang Zhang; Chen Gong; Zihan Yang; Fan Wei; Xin Sun; Jie Ji; Yushun Zeng; Chi-feng Chang; Xunan Liu; Deepthi S. Rajendran Nair; Biju B. Thomas; Qifa Zhou (Bioengineering, 2024)
Functional ultrasound (fUS) flow imaging provides a non-invasive method for the in vivo study of cerebral blood flow and neural activity. This study used functional flow imaging to investigate rat brain’s response to ultrasound and colored-light stimuli. Male Long-Evan rats were exposed to direct full-field strobe flashes light and ultrasound stimulation to their retinas, while brain activity was measured using high-frequency ultrasound imaging. Our study found that light stimuli, particularly blue light, elicited strong responses in the visual cortex and lateral geniculate nucleus (LGN), as evidenced by changes in cerebral blood volume (CBV). In contrast, ultrasound stimulation elicited responses undetectable with fUS flow imaging, although these were observable when directly measuring the brain’s electrical signals. These findings suggest that fUS flow imaging can effectively differentiate neural responses to visual stimuli, with potential applications in understanding visual processing and developing new diagnostic tools.